Jab planter service provision model for smallholder mechanization in Kenya - Waswa, Boaz; Mutai, Weldone; Mkomwa, Saidi; Kuria, Peter; Ooro, Patrick (2024)
Conservation agriculture (CA) is a critical approach that aims to balance agricultural productivity with environmental sustainability. Mechanization (especially power units, seeders, rippers and sprayers) is a key input for CA. Unfortunately, majority of smallholder farmers often have difficulties accessing and using appropriate and affordable mechanization solutions. There is a need to build sustainable agricultural mechanization models that can meet needs of farmers of all sizes, both small-, medium- and largescale and for the different farm operations. This can be done by equipping and training CA service provision entrepreneurs. Such entrepreneurs can make a livelihood by supplying high quality CA and other mechanization services to the farmers in their regions. This technical bulletin presents a description of the Jab Planter Service Provision Model for Smallholder Mechanization in Kenya and highlights the successful work by Pauline Mogambi, an entrepreneur offering jab planter services to farmers in Nakuru County.